Progressive renal injury from transgenic expression of human carbonic anhydrase IV folding mutants is enhanced by deficiency of p58(IPK) - Datta, Rupak (National Academy of Sciences, 2010)
Mutations in the human carbonic anhydrase IV (hCAIV) have been associated with retinal degeneration in an autosomal-dominant form of retinitis pigmentosa (RP17). Prior in vitro cell culture studies confirmed that all of the RP17-associated hCAIV mutations cause protein misfolding, leading to endoplasmic reticulum (ER) stress–induced apoptosis in cells expressing the mutant proteins. To evaluate the physiological impacts of these folding mutants in other carbonic anhydrase IV–producing tissues, we generated two transgenic mouse lines expressing R219S or R14W hCAIV under control of the endogenous hCAIV promoter. Expression of either of these mutant proteins in kidneys caused progressive renal injury in male transgenic mice as evidenced by an age-dependent increase in the tubule cell apoptosis starting at approximately 20 weeks of age and vacuolization throughout the renal cortex in older mice. Up-regulation of the ER chaperone, BiP, was observed in the cells of the renal cortex of the male transgenic mice, suggesting ER stress as a causal factor for the renal injury. The renal injury inflicted by expression of the folding mutants was markedly enhanced by haploinsufficiency of the ER cochaperone p58(IPK). The transgenic mice expressing the hCAIV folding mutants on a p58(IPK) heterozygous background showed extensive renal tubular apoptosis by approximately 10 weeks of age in both male and female mice. These data indicate that expression of the RP17-associated folding mutants of hCAIV can adversely affect tissues beyond the retina and their in vivo proteotoxicity is sensitive to modulation of the protein folding environment of the ER.